Are the nationally determined contributions of African countries just negotiation documents? - Ole Winckler Andersen; Rasmus Hundsbæk Pedersen (Danish Institute for International Studies (DIIS), 2024)
All countries in Sub-Saharan Africa have submitted Nationally Determined Contributions (NDCs) as part of their respective commitments to climate action, and they will start to share updated versions of their NDCs in 2025. While various analyses have documented and analysed the significant differences in countries' NDCs, there has only been a limited focus on this aspect of African countries' NDCs or on the role NDCs play in these countries. This paper addresses this issue by exploring common trends and differences in the NDCs of countries in SubSaharan Africa and discusses some potential explanations. The paper argues that the contents of these NDCs are not only influenced by climate-change considerations but also by a complex set of national and international factors. A better understanding of the differences between them in Sub-Saharan Africa is needed, including the extent to which the NDCs constitute commitment or negotiation positions of the countries.
Keywords: 330; Sub-Saharan Africa; NDCs; Nationally Determined Contributions; COP29; climate; climate-change; Paris Agreement